2005
DOI: 10.1103/physrevlett.94.090405
|View full text |Cite
|
Sign up to set email alerts
|

Atom Michelson Interferometer on a Chip Using a Bose-Einstein Condensate

Abstract: An atom Michelson interferometer is implemented on an "atom chip." The chip uses lithographically patterned conductors and external magnetic fields to produce and guide a Bose-Einstein condensate. Splitting, reflecting, and recombining of condensate atoms are achieved by a standing-wave light field having a wave vector aligned along the atom waveguide. A differential phase shift between the two arms of the interferometer is introduced by either a magnetic-field gradient or with an initial condensate velocity. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
360
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 377 publications
(365 citation statements)
references
References 22 publications
4
360
0
1
Order By: Relevance
“…In a recent experiment [1], it was observed that a sequence of two standing wave square pulses can split a BEC at rest into +/-2 k diffraction orders with almost 100% efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent experiment [1], it was observed that a sequence of two standing wave square pulses can split a BEC at rest into +/-2 k diffraction orders with almost 100% efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…
Abstract:In a recent experiment [1], it was observed that a sequence of two standing wave square pulses can split a BEC at rest into +/-2 k diffraction orders with almost 100% efficiency.By truncating the Raman-Nath equations to a 2-state model, we provide an intuitive picture that explains this double square pulse beamsplitter scheme. We further show it is possible to optimize a standingwave multi square pulse sequence to efficiently diffract an atom at rest to symmetric superposition of +/-2n k diffraction order with n>1.
…”
mentioning
confidence: 99%
“…Since the GPE itself is nonlinear Schrödinger equation (NLSE) with pseudo potential, the solution like soliton has unique characteristics. Some authors have deeply considered the NLSE and founded that the equation has been used to consider not only in atom laser, but also in some areas of active researches, for example pulse propagation in nonlinear optics and twin-core optical optics [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the classical optical Sagnac effect [1][2][3][4], which measures rotation rate along an axis, is being exploited in all modern rotation sensors [5] and their applications to inertial navigation systems [6]. Even more recently, much effort has been expended on experiments with quantum Sagnac interferometers, using single-photons [7], using cold atoms [8,9] and using Bose-Einstein condensates(BEC) [10][11][12], in efforts to improve the sensitivity to rotation of the classical optical Sagnac effect, and schemes have also been proposed to improve the sensitivity of rotation sensing using multi-photon correlations [13] and using entangled particles, which are expected to have Heisenberg limited precision that scales as 1/N , where N is the number of particles [14]. Limitations of classical gyroscopes have been discussed in Ref [5] and limits of classical Sagnac effects has been discussed in terms of Shannon mutual information in Ref [15].…”
Section: Introductionmentioning
confidence: 99%